Pengaruh Literasi Keuangan Syariah Terhadap Penggunaan Qris Pada Pedagang Muslim - Muhammad Ilyas (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of Islamic financial literacy on the use of the Quick Response Code Indonesian Standard (QRIS) among Muslim merchants. The research employs a qualitative descriptive approach, conducted at Sangkumpal Bonang Market, Padangsidimpuan City. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that Islamic financial literacy plays a central role in enhancing merchants’ acceptance of QRIS. Merchants who understand the basic principles of Islamic financial transactions—such as the prohibition of riba, the obligation of trustworthiness in wealth management, and fairness—are more likely to adopt digital payment innovations. Conversely, low levels of literacy hinder the adoption of cashless payment technologies. From the perspective of the Qur’an, the use of QRIS can be linked to the command of recording transactions (QS. Al-Baqarah [2]: 282), the prohibition of usury (QS. Al-Baqarah [2]: 275), and the injunction against consuming wealth unjustly (QS. An-Nisa [4]: 29). These principles reinforce the relevance of QRIS to the objectives of Islamic law (maqashid al-shariah), particularly hifz al-mal (protection of wealth), while also supporting security (hifz al-nafs), rational financial management (hifz al-‘aql), and family welfare sustainability (hifz al-nasl). The study concludes that Islamic financial literacy functions not only as a technical skill but also as a spiritual foundation guiding merchants to utilize financial technology in a lawful, safe, and productive manner.